Roadmap for cardiovascular education across the European Society of Cardiology: inspiring better knowledge and skills, now and for the future. (31st January 2018) - Kotecha, Dipak; Bax, Jeroen J; Carrera, Céline; Casadei, Barbara; Merkely, Bela; Anker, Stefan D; Vardas, Panos E; Kearney, Peter P; Roffi, Marco; Ros, Michelle; Vahanian, Alec; Weidinger, Franz; et al.
Abstract: Aims: The provision of high-quality education allows the European Society of Cardiology (ESC) to achieve its mission of better cardiovascular practice and provides an essential component of translating new evidence to improve outcomes. Methods and results: The 4th ESC Education Conference, held in Sophia Antipolis (December 2016), brought together ESC education leaders, National Directors of Training of 43 ESC countries, and representatives of the ESC Young Community. Integrating national descriptions of education and cardiology training, we discussed innovative pathways to further improve knowledge and skills across different training programmes and health care systems. We developed an ESC roadmap supporting better cardiology training and continued medical education (CME), noting: (i) The ESC provides an excellent framework for unbiased and up-to-date cardiovascular education in close cooperation with its National Societies. (ii) The ESC should support the harmonization of cardiology training, curriculum development, and professional dialogue and mentorship. (iii) ESC congresses are an essential forum to learn and discuss the latest developments in cardiovascular medicine. (iv) The ESC should create a unified, interactive educational platform for cardiology training and continued cardiovascular education combining Webinars, eLearning Courses, Clinical Cases, and other educational programmes, along with ESC Congress content, Practice Guidelines and the next ESC Textbook of Cardiovascular Medicine. (v) ESC-delivered online education should be integrated into National and regional cardiology training and CME programmes. Conclusion: These recommendations support the ESC to deliver excellent and comprehensive cardiovascular education for the next generation of specialists. Teamwork between international, national and local partners is essential to achieve this objective.